2020
DOI: 10.1109/tcomm.2020.3022896
|View full text |Cite
|
Sign up to set email alerts
|

Cache-Enabled Millimeter Wave Cellular Networks With Clusters

Abstract: Wireless content caching in cellular networks is an efficient way to reduce the service delay and alleviate backhaul pressure. For the benefits of sharing spectral and storage resources, clustering in cached networks has recently attracted significant research interests. Meanwhile, since the multimedia content (e. g.., video) of caching networks may require a huge transmission rates, millimeter wave (mmWave) communication is considered to be an efficient transmission scheme for cacheenabled networks. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Authors in [52] proposed a method to solve the joint problem considering time RA, user association, and mmWave beamforming. In [53], using mmWave communication improve the average service delay in a cellular network.…”
Section: Millimeter Wave (Mmwave)mentioning
confidence: 99%
“…Authors in [52] proposed a method to solve the joint problem considering time RA, user association, and mmWave beamforming. In [53], using mmWave communication improve the average service delay in a cellular network.…”
Section: Millimeter Wave (Mmwave)mentioning
confidence: 99%
“…For tractbility of analysis, the perfect beamforming is assumed between the transmitter and receiver [41]. Based on the above analysis, we can derive the the signal to interference plus noise ratio expression of a typical user from the associated SBS or the associated MBS via wireless access link at the distance r as follows.…”
Section: Channel and Transmission Modelmentioning
confidence: 99%
“…The disadvantage of this algorithm is that it is unable to achieve the same performance as the corresponding supervised ML one. Moreover, in (Huang S. et al, 2020), the authors studied the use of extreme learning machine for jointly optimizing transmit and receive hybrid beamforming in MU-MIMO wireless systems. The algorithm requires as inputs the real and imaginary parts of the MIMO channel coefficients and returns the an optimal beamforming vectors estimation.…”
Section: Mac and Rrm Layermentioning
confidence: 99%
“…The main idea is to proactively transfer the content to be requested by a single of a cluster of UEs to the nearest possible BS/AP. Towards this direction, several researchers presented ML-based caching policies (Cheng et al, 2019;Jiang et al, 2019;Saputra et al, 2019;Wang X. et al, 2020;Kirilin et al, 2020;Ye et al, 2020). Specifically, in (Ye et al, 2020), the authors reported a device to primary and secondary BS clustering approach based on the requested content location in mmW ultra-dense wireless networks.…”
Section: Transport Layermentioning
confidence: 99%
See 1 more Smart Citation